2019
DOI: 10.1126/science.aaw2843
|View full text |Cite
|
Sign up to set email alerts
|

Large plasticity in magnesium mediated by pyramidal dislocations

Abstract: Lightweight magnesium alloys are attractive as structural materials for improving energy efficiency in applications such as weight reduction of transportation vehicles. One major obstacle for widespread applications is the limited ductility of magnesium, which has been attributed to c+a<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…As the onset of P → B transformation depends on the normal stresses on the prismatic/basal planes which, in most cases, translate to both a resolved shear stress and a normal stress on the twinning plane, twinning nucleation by the dual-step mechanism can also be critically affected by the normal stress on the twinning plane. Finally, a major advantage of nanoscale samples over bulk sample is that high-stress states can be attained 54 ; localized stress concentrations within bulk samples may provide equivalent stress condition for the activation of the dual-step mechanism. Moreover, our findings provide a solid fundamental basis for the twinning-based design and processing of advanced HCP alloys.…”
Section: Discussionmentioning
confidence: 99%
“…As the onset of P → B transformation depends on the normal stresses on the prismatic/basal planes which, in most cases, translate to both a resolved shear stress and a normal stress on the twinning plane, twinning nucleation by the dual-step mechanism can also be critically affected by the normal stress on the twinning plane. Finally, a major advantage of nanoscale samples over bulk sample is that high-stress states can be attained 54 ; localized stress concentrations within bulk samples may provide equivalent stress condition for the activation of the dual-step mechanism. Moreover, our findings provide a solid fundamental basis for the twinning-based design and processing of advanced HCP alloys.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be noted that the proposed effects of the alloying elements are based exclusively on first-principles DFT calculations, as discussed in section A on pyramidal stacking faults, and they have not been examined by any MD simulations due to the lack of inter-atomic potentials for magnesium alloys. A very recent work based on in-situ transmission electron microscope mechanical testing, 3D image reconstruction, and atomistic simulations [38] demonstrated that the c þ a h i edge dislocation in pure Mg can glide on both pyramidal I and pyramidal II planes. A separate study of dislocations using weakbeam dark-field transmission electron microscopy reported that c þ a h i dislocations do not dissociate in hot-rolled AZ31 (Mg-3Al-1Zn-0.3Mn; wt pct) alloy.…”
Section: B Slip Twinning and Grain Boundary Slidingmentioning
confidence: 99%
“…This high stress coupled with promoted plasticity was also recently observed in microcompression of Mg with limited ductility at large scales. 55 Furthermore, the amorphous surface layer in FIB-machined pillars hinders surface selfdiffusion for dislocation nucleation and increases the required activation energy and activation volume 56 . The incoherent interface between crystalline core and amorphous shell also constricts the escape of dislocations at the surface, which then generates a back-stress which induces dislocation pile-ups and crack formation 57 .…”
Section: Discussionmentioning
confidence: 99%